Grade of the inner cell mass, but not trophectoderm, predicts live birth in fresh blastocyst single transfers. (1st October 2016) - Subira, Jessica; Craig, Jo; Turner, Karen; Bevan, Aysha; Ohuma, Eric; McVeigh, Enda; Child, Tim; Fatum, Muhammad
Abstract: Debate continues over which morphological parameter is most important in selecting blastocysts for transfer. We aimed to investigate which parameter more accurately predicts the occurrence of a live birth by designing a retrospective cohort study of 1084 fresh elective single blastocyst transfers. Primary outcome was live birth rate (LBR) and secondary outcomes were implantation, clinical pregnancy and early pregnancy loss rates. Blastocyst expansion and inner cell mass (ICM), but not trophoectoderm, were associated with LBR in the definitive multivariable regression analysis. When ICM grade dropped from A to C the likelihood of achieving a live birth was reduced by 55% (OR= 0.45, 95% CI 0.26-0.79, p = .005). These results were similar for clinical pregnancy rates. Early pregnancy loss rates of embryos with ICM grade C were more than double (38.0%) compared to those of grades A (15.95%) and B (17.17%, p = .002). The transfer of an embryo with an optimal inner cell mass reduces early pregnancy loss and increases the likelihood of a live birth. We did not find any significant association between trophectoderm and LBR in the multivariable analysis in contrast with recent studies.